Evaluation of Temperature, Resistance, Power Loss, and Voltage Drop in CCO, Connector, and Winding Cable Joints at ULP Cirebon City - Arief Rachmansyach Haidar; Taryo Taryo (Jambura Journal of Electrical and Electronics Engineering, 2026)
This study aims to evaluate the electrical properties of aluminum CCO cable splicing methods, connectors, and wraps in the low-voltage distribution network at the Graha Alana Klayan (GAKA) distribution substation under the jurisdiction of PT PLN (Persero) ULP Cirebon Kota. In this study, NFA2X cable with a cross-sectional area of 70 mm² and a length of 125 meters was used, connected to a 250 kVA distribution transformer. Measurements were conducted under off-peak (LWBP) and peak load (WBP) conditions, involving current, temperature, and voltage parameters measured using a clamp meter and a thermal camera. The data obtained from these measurements were used to calculate the resistance, power loss, and voltage drop for each connection method analyzed. The findings of this study indicate that the aluminum CCO connection exhibits the highest power loss and voltage drop compared to connectors and splices. The power loss values for the aluminum CCO connection were recorded at 26.64 W during LWBP and 35.23 W during WBP, while for the connector they were 2.37 W and 5.91 W, and the spliced connection showed values of 2.23 W and 5.84 W. The highest voltage drop was also recorded for the aluminum CCO connection, namely 1.17 V at LWBP and 1.35 V at WBP. The results of this study indicate that the characteristics of cable joints and load conditions affect the efficiency and reliability of the electrical power distribution system. Based on the study, power losses and voltage drops are influenced by cable joints and uneven load currents across each phase of the distribution system.